Relation of leisure time, occupational, domestic, and commuting physical activity to health indicators in Europe. - Abu-Omar, Karim; Rütten, Alfred (Preventive Medicine, 2008)
Objectives: To investigate relationships between physical activities in different domains (leisure time, occupational, domestic, commuting) and health indicators (self-rated health, body mass index). Methods: The short version of the International Physical Activity Questionnaire (IPAQ) and additional questions on domain specific physical activity were submitted face-to-face to 29,193 individual's age 15 years and older in the 27 member states of the Europe Union, 2 affiliated nations (Croatia, Turkey), and Cyprus North in 2005 as part of Eurobarometer 64.3. Results: Leisure time physical activity (compared to no leisure time physical activity) was positively associated with self-rated health (males: Odds Ratio (OR) = 2.85, 95% Confidence Interval (CI): 2.27, 3.58; females: OR = 2.77, 95% C.I. 2.16, 3.56) and inversely with obesity (males: OR = 0.65, 95% C.I. 0.50, 0.83; females: OR = 0.46, 95% C.I. 0.34, 0.63). Being in the highest quartile of the total volume of physical activity expressed using metabolic equivalents (in MET-min/week) (compared to being in the lowest quartile) was not related to self-rated health (males: OR = 0.99, 95% C.I. 0.81, 1.21; females: OR = 1.19, 95% C.I 0.98, 1.43) or obesity (males: OR = 1.25, 95% C.I., 0.99, 1.59; females: OR = 1.26, 95% C.I. 1.02, 1.57). Gender-specific effects were observed for other domains of physical activity. Analysis on national levels showed pronounced relationships of leisure time physical activity to health indicators. Conclusions: Domains of physical activity being related to health indicators, they may pertain to surveillance. © 2008 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.phil.dps.iss.lsw.relati
Keywords: Body mass index; Commuting; Domestic physical activity; European Union; Global physical activity questionnaire; International physical activity questionnaire; Leisure time physical activity; Obesity; Occupational physical activity; Physical activity; Self-rated health; Surveillance